Nineteen‐channel receive array and four‐channel transmit array coil for cervical spinal cord imaging at 7T. Issue 1 (July 2014) - Zhao, Wei; Cohen‐Adad, Julien; Polimeni, Jonathan R.; Keil, Boris; Guerin, Bastien; Setsompop, Kawin; Serano, Peter; Mareyam, Azma; Hoecht, Philipp; Wald, Lawrence L.
<x xml:space="preserve">Abstract</x> Purpose To design and validate a radiofrequency (RF) array coil for cervical spinal cord imaging at 7T. Methods A 19‐channel receive array with a four‐channel transmit array was developed on a close‐fitting coil former at 7T. Transmit efficiency and specific absorption rate were evaluated in a B1+ mapping study and an electromagnetic model. Receive signal‐to‐noise ratio (SNR) and noise amplification for parallel imaging were evaluated and compared with a commercial 3T 19‐channel head–neck array and a 7T four‐channel spine array. The performance of the array was qualitatively demonstrated in human volunteers using high‐resolution imaging (down to 300 μm in‐plane). Results The transmit and receive arrays showed good bench performance. The SNR was approximately 4.2‐fold higher in the 7T receive array at the location of the cord with respect to the 3T coil. The g‐factor results showed an additional acceleration was possible with the 7T array. In vivo imaging was feasible and showed high SNR and tissue contrast. Conclusion The highly parallel transmit and receive arrays were demonstrated to be fit for spinal cord imaging at 7T. The high sensitivity of the receive coil combined with ultra‐high field will likely improve investigations of microstructure and tissue segmentation in the healthy and pathological spinal cord. Magn Reson Med 72:291–300, 2014. © 2013 Wiley Periodicals, Inc.